x → 0 lim x ( 1 + x ) 1 / x − e = ?
Round your answer to 1 decimal place.
Clarification
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Or we can use the mclaurin series for both terms in the numerator.
This can be done by using L'Hopital rule repeatedly. First we find the derivative of ( 1 + x ) 1 / x . Here, I don't show you, but you can try by taking y = ( 1 + x ) 1 / x and differentiate the equation lo g y = x 1 lo g ( 1 + x ) . Since the limit is of the indeterminate form 0 / 0 , we take derivative and get x → 0 lim [ x ( x + 1 ) 1 − x 2 1 lo g ( 1 + x ) ] ( 1 + x ) 1 / x = x → 0 lim [ x 2 ( x + 1 ) x − ( x + 1 ) lo g ( 1 + x ) ] ⋅ ( 1 + x ) 1 / x . What I'll show is that limit as x → 0 of the expression in the bracket is − 1 / 2 , so that I can split the limit into product of two limits ( ∗ ) . x → 0 lim x 2 ( x + 1 ) x − ( x + 1 ) lo g ( 1 + x ) = x → 0 lim 3 x 2 + 2 x − lo g ( 1 + x ) = x → 0 lim 6 x + 2 − 1 / ( 1 + x ) = − 2 1 . Note that in each step, except the last one, it is of the form 0 / 0 , so that we can take derivative on both part. Additionally, by substituting n = 1 / x in the definition of e , we see that lim x → 0 + ( 1 + x ) 1 / x = e . Therefore, the answer is − 2 e ≈ − 1 . 4 .
( ∗ ) If the limit is of the form lim f ( x ) ⋅ g ( x ) , we need to show FIRST that both lim f ( x ) and lim g ( x ) exist. Then we can conclude that lim f ( x ) ⋅ g ( x ) = ( lim f ( x ) ) ⋅ ( lim g ( x ) ) .
Problem Loading...
Note Loading...
Set Loading...
Or you can use the series